A new analytic framework for identifying tour routes service innovation in e-commerce platform using knowledge graph. (20th January 2023) - Zhang, Shuang; Zhu, Zhen
While the growth of the tourism market has created significant market opportunities for tour routes developers to improve service innovation, it has inevitably induced other travel agencies to imitate. However, there has been little rigorous research to identify service innovation from a knowledge graph perspective. This study presents a knowledge graph framework to identify service innovations of tour routes, which can tackle the measurement challenges of knowledge representation in different dimensions. A knowledge graph-based method for service products is employed to obtain the dynamic weight of dimensions, aimed at calculating the importance of graph network nodes through knowledge extraction after division of dimensions. This study shows that the proposed approach can accurately determine the level of service innovation, providing a benchmark for exploring refined knowledge representation in products' unstructured attributes.